Empagliflozin and health-related quality of life outcomes in patients with heart failure with reduced ejection fraction: the EMPEROR-Reduced trial. (9th January 2021) - Butler, Javed; Anker, Stefan D; Filippatos, Gerasimos; Khan, Muhammad Shahzeb; Ferreira, João Pedro; Pocock, Stuart J; Giannetti, Nadia; Januzzi, James L; Piña, Ileana L; Lam, Carolyn S P; Ponikowski, Piotr; Sattar, Naveed; et al.
Abstract: Aims: In this secondary analysis of the EMPEROR-Reduced trial, we sought to evaluate whether the benefits of empagliflozin varied by baseline health status and how empagliflozin impacted patient-reported outcomes in patients with heart failure with reduced ejection fraction. Methods and results: Health status was assessed by the Kansas City Cardiomyopathy Questionnaires-clinical summary score (KCCQ-CSS). The influence of baseline KCCQ-CSS (analyzed by tertiles) on the effect of empagliflozin on major outcomes was examined using Cox proportional hazards models. Responder analyses were performed to assess the odds of improvement and deterioration in KCCQ scores related to treatment with empagliflozin. Empagliflozin reduced the primary outcome of cardiovascular death or heart failure hospitalization regardless of baseline KCCQ-CSS tertiles [hazard ratio (HR) 0.83 (0.68–1.02), HR 0.74 (0.58–0.94), and HR 0.61 (0.46–0.82) for <62.5, 62.6–85.4, and ≥85.4 score tertiles, respectively; P -trend = 0.10]. Empagliflozin improved KCCQ-CSS, total symptom score, and overall summary score at 3, 8, and 12 months. More patients on empagliflozin had ≥5-point [odds ratio (OR) 1.20 (1.05–1.37)], 10-point [OR 1.26 (1.10–1.44)], and 15-point [OR 1.29 (1.12–1.48)] improvement and fewer had ≥5-point [OR 0.75 (0.64–0.87)] deterioration in KCCQ-CSS at 3 months. These benefits were sustained at 8 and 12 months and were similar for other KCCQ domains. Conclusion: Empagliflozin improved cardiovascular death or heart failure hospitalization risk across the range of baseline health status. Empagliflozin improved health status across various domains, and this benefit was sustained during long-term follow-up. Clinical trial registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03057977. Graphical abstract: